Employment quality of senior citizens in Chile, an active aging factor - Ferrada-Bórquez, Luz María; Ferrada-Bórquez, Mauricio Alejandro (Papeles de Población, 2018)
Chile´s population is aging at an increasing rate, accompanied by the rising participation of senior citizens in the labor market. The aim of this study is to determine the employment conditions of the elderly in Chile. To this end, partial and synthetic indicators are estimated that reveal the situation with regard to the following factors: social security, contractual arrangements, working hours and income. Significant variations are obtained in the estimated indices between men and women, different educational levels, geographic area of residence, company size and economic sector in which people are employed. In turn, the greatest disparities were observed in social security and employment contract conditions. These results enable us to argue the case for focused public policies in the context of a new paradigm of active aging.